2019
DOI: 10.1016/j.jacep.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Randomized Controlled Trials of Atrial Fibrillation Ablation With Pulmonary Vein Isolation Versus Without

Abstract: Objectives This meta-analysis examined the ability of pulmonary vein isolation (PVI) to prevent atrial fibrillation in randomized controlled trials (RCTs) in which the patients not receiving PVI nevertheless underwent a procedure. Background PVI is a commonly used procedure for the treatment of atrial fibrillation (AF), and its efficacy has usually been judged against therapy with anti-arrhythmic drugs in open-label trials. There have been several RCTs of AF ablation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Isolation of the pulmonary veins has always been the focus of the CA strategies [ 94 , 104 ]. Thus, it is not surprising that non-PVI strategies were not as efficient as PVI in this NMA, consistent with previous studies [ 4 , 68 , 105 ]. However, this NMA also showed that adding complementary therapies to PVI, such as GP ablation [ 52 ], RDN [ 77 ], or performing additional ablation [ 28 , 85 ] can increase procedural efficacy.…”
Section: Discussionsupporting
confidence: 92%
“…Isolation of the pulmonary veins has always been the focus of the CA strategies [ 94 , 104 ]. Thus, it is not surprising that non-PVI strategies were not as efficient as PVI in this NMA, consistent with previous studies [ 4 , 68 , 105 ]. However, this NMA also showed that adding complementary therapies to PVI, such as GP ablation [ 52 ], RDN [ 77 ], or performing additional ablation [ 28 , 85 ] can increase procedural efficacy.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence and incidence of atrial fibrillation (AF) increase with age [1]. AF can also be observed in the young with or without structural heart disease [2,3]. Over the last 3 decades, catheter ablation has evolved as an effective treatment modality for patients with AF.…”
mentioning
confidence: 99%
“…In AF patients undergoing PVI ablation, 29.4-42% of patients developed ATAs during the follow-up period. [36][37][38] However, in AFL patients, the ATAs can be found in 16.7-50% of patients after CTI ablation. 39,40 The Link Between Atrial Flutter and AF…”
Section: Main Results and The Current Recommendationmentioning
confidence: 99%